Identification of Difficulties of Physics Education Student Faculty of Teacher Training & Education in Online Learning Process On Covid-19 Pandemic Era - Wahyuni, Agus; Wulandari, Sri; Farhan, Ahmad; Rizal, Syamsul (UIN Fatmawati Sukarno Bengkulu, 2022)
Online thesis guidance is an obstacle faced by students majoring in physics education, FKIP USK. This qualitative descriptive study aims to find out what difficulties affect the student learning process through online learning for Physics Education students. The sample in this study were all Physics Education students who carried out online learning, totaling 54 respondents. Data collection was obtained by using a questionnaire to determine learning difficulties in the online learning process. The data analysis technique used to determine the percentage of learning difficulties is sorting the data according to research indicators including internal factors, namely physical and psychological barriers, external factors, namely barriers to educators (lecturers), facilities, families, and extracurriculars. The results of data analysis showed that learning difficulties with percentages were physical barriers (61.1%), psychological barriers (56.7%), educators (lecturers) (58.7%), facilities (53.6%) ), family (49.7%), and extracurricular (47.4%). So it can be concluded that the main factor that affects the difficulty in the learning process is internal physical barriers